2017
DOI: 10.1016/j.lithos.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sources of the Early Mesozoic Gouli batholith, Eastern Kunlun Orogenic Belt, northern Tibetan Plateau: Linking continental crustal growth with oceanic subduction

Abstract: Orogenic belts have been among the most important locations to investigate the growth of continental crust (CC). The Eastern Kunlun Orogenic Belt (EKOB), which contains widespread Permian-Triassic granitoids, is volumetrically comparable to the Cenozoic Gangdese magmatic belt in the Tibetan Plateau and is an ideal region to investigate the mechanism of the Paleozoic-Mesozoic CC growth in this region. The Gouli batholith at the eastern end of the EKOB consists of the synchronous Xiangride granodiorite, Asiha qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 74 publications
4
67
0
Order By: Relevance
“…This region experienced subduction and collisional orogeny from the Late Permian to the Early Triassic as the Buqingshan-A'nemaqen Ocean, part of the Paleo-Tethys Ocean, generated northward subduction, which triggered crust-mantle magmatic activity and led to the emplacement of a large number of arc magmatic rocks that are linearly distributed across the region [6,16]. The inferred EKOB tectonic evolution indicates that the Late Triassic granitoids that formed after subduction were related to collisional to post-collisional tectonic processes [4,14,18]. This tectonic movement was related to the formation of porphyry-skarn type Cu-Mo-Au deposits.…”
Section: Timing Of Magmatism and Mineralizationmentioning
confidence: 98%
See 1 more Smart Citation
“…This region experienced subduction and collisional orogeny from the Late Permian to the Early Triassic as the Buqingshan-A'nemaqen Ocean, part of the Paleo-Tethys Ocean, generated northward subduction, which triggered crust-mantle magmatic activity and led to the emplacement of a large number of arc magmatic rocks that are linearly distributed across the region [6,16]. The inferred EKOB tectonic evolution indicates that the Late Triassic granitoids that formed after subduction were related to collisional to post-collisional tectonic processes [4,14,18]. This tectonic movement was related to the formation of porphyry-skarn type Cu-Mo-Au deposits.…”
Section: Timing Of Magmatism and Mineralizationmentioning
confidence: 98%
“…The East Kunlun Orogenic Belt (EKOB) is located along the northern margin of the Tibetan Plateau [1][2][3] and is one of the most important magmatic arcs and polymetallic metallogenic belts in China [4][5][6][7][8]. Many porphyry-skarn deposits have been discovered and explored in this area (e.g., the Kaerqueka Cu-Mo porphyry deposit, Hutouya Cu-Pb-Zn skarn deposit, and Galinge Fe skarn deposit [9][10][11][12][13]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the timing of closure of the A'nyemaqen Ocean remains contentious. Yin and Zhang () and Huang et al () suggested that the A'nyemaqen Ocean closed in the Late Permian, whereas others argued that the cessation of subduction occurred in the Early Triassic (Shao et al, ; Yang, Xu, Li, & Shi, ), Middle Triassic (J. J. Chen et al, ; Li et al, ; Liu et al, ; Pei et al, ; Xia et al, ; Xiong et al, ; Zhang, Ma, Xiong, & Liu, ), or even Late Triassic (Roger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the EKO records the history of the Proto‐Tethys‐related and Paleo‐Tethys‐related orogenesis (Hu et al, ; H. F. Yin & Zhang, ). A multitude of studies over the past decades focused on the tectonic evolution of Tethys orogenic system (J. J. Chen et al, ; Jiang et al, ; B. Liu et al, ; Mo et al, ; Şengör, ; R. Xia et al, ; Xiong, Ma, Zhang, Liu, & Jiang, ; Xu et al, ; Xu, Yang, Li, & Yao, ; H. F. Yin & Zhang, ). The timing of Proto‐Tethys Ocean closure remains controversial in the EKO: (a) Mo et al () considered that the Proto‐Tethys‐related Ocean closed in the Late Ordovician based on the Ar‐Ar ages of gabbro in the Tumuleke.…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of studies over the past decades focused on the tectonic evolution of Tethys orogenic system (J. J. Chen et al, 2017;Jiang et al, 1992;B. Liu et al, 2012;Mo et al, 2007;Şengör, 1984;Xiong, Ma, Zhang, Liu, & Jiang, 2014;Xu et al, 2007;Xu, Yang, Li, & Yao, 2006;H.…”
Section: Introductionmentioning
confidence: 99%